Highly improved toluene gas-sensing performance of mesoporous Co3O4 nanowires and physical mechanism. (August 2021) - Wang, L.; Song, S.Y.; Hong, B.; Xu, J.C.; Han, Y.B.; Jin, H.X.; Jin, D.F.; Li, J.; Yang, Y.T.; Peng, X.L.; Ge, H.L.; Wang, X.Q.
Graphical abstract: Highlights: Co3 O4 -DNWs were separated from Co3 O4 -BNWs by the centrifugation technique. Both samples present the same mesoporous-structure, diameter and similar defects. Microstructures of Co3 O4 nanowires greatly affect the toluene gas sensitivity. Both samples with high surface area present the higher response than others'. The gas-sensing mechanism results from the surface oxygen and toluene adsorption. Abstract: Mesoporous Co3 O4 nanowires were synthesized with the nanocasting method, and then the dispersed Co3 O4 nanowires (Co3 O4 -DNWs) were separated from the bundled Co3 O4 nanowires (Co3 O4 -BNWs) by the centrifugation technique. From the characterization with TEM, X-ray diffraction, UV–vis spectra and nitrogen adsorption-desorption isotherm, both samples present the same mesoporous-structure, diameter and the similar defects due to the same synthesis conditions. All results indicate that the microstructures and morphology of Co3 O4 nanowires greatly affect the toluene gas sensing performance. Owing to the mesoporous-structures with the high surface area, the sensitivities of both samples are higher than others'. Co3 O4 -DNWs exhibit the higher specific surface area (44.98 m 2 g −1 ) than Co3 O4 -BNWs, leading to the excellent gas-sensing properties to toluene gas at the optimized operating temperature of 210℃. Moreover, both samples present the excellent stability and selectivity to toluene gas. The gas-sensing mechanism results from the surface oxygen and toluene gas adsorption through comparing the sensitivity of Co3 O4 -DNWs and Co3 O4 -BNWs.